Some Formulas for New Quadruple Hypergeometric Functions - Jihad A. Younis; Hassen Aydi; Ashish Verma (Journal of Mathematics)
In this paper, we aim to introduce six new quadruple hypergeometric functions. Then, we investigate certain formulas and representations for these functions such as symbolic formulas, differential formulas, and integral representations.